Morphofunctional Traits and Pollination Mechanisms of Coronilla emerus L. Flowers (Fabaceae). (30th April 2012) - Aronne, Giovanna; Giovanetti, Manuela; De Micco, Veronica
Abstract : It is accepted that the papilionaceous corolla of the Fabaceae evolved under the selective pressure of bee pollinators. Morphology and function of different parts of Coronilla emerus L. flowers were related to their role in the pollination mechanism. The corolla has a vexillum with red nectar lines, a keel hiding stamens and pistil, and two wing petals fasten to the keel with two notched folds. Pollinators land on the complex of keel and wings, trigger the protrusion of pollen and finally of the stigma from the keel tip. Data on pollen viability and stigma receptivity prove that flowers are proterandrous. The results of hand-pollination experiments confirmed that insects are fundamental to set seed. Interaction with pollinators allows not only the transport of pollen but also the rupture of the stigmatic cuticle, necessary to achieve both allogamy and autogamy. Field observations showed that Hymenoptera, Lepidoptera, and Diptera visited the flowers. Only some of the Hymenoptera landed on the flowers from the front and elicited pollination mechanisms. Most of the insects sucked the nectar from the back without any pollen transfer. Finally, morphological and functional characteristics of C. emerus flowers are discussed in terms of floral larceny and reduction in pollination efficiency.